A 37 nW MOSFET-Only Voltage Reference in 0.13 um CMOS - de Lima, Vanessa; Klimach, Hamilton (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
This work presents the design of a MOS-only voltage reference with nano-watt power consumption. The proposed circuit consists of a threshold voltage monitor circuit cascaded with a high-slope proportional to absolute temperature (PTAT) voltage generator. The operation of the circuit is analytically described and a design methodology is presented. The proposed circuit was designed and simulated in a standard 130 nm CMOS process while consuming just 37 nW under 1.2 V of power supply at room temperature. Simulation results present a 585 mV reference voltage with a typical temperature coefficient (TC) of 10.13 ppm/°C, for a temperature range from −40 to 125 °C, a power supply rejection ratio (PSRR) of −54.41 dB at 100 Hz, and a line sensitivity of 0.071 %/V was found for a supply range from 1 V to 1.8 V. Monte-Carlo simulations are presented to evaluate the sensitivity to fabrication variability. The estimated silicon area is 0.0078 mm 2 .